2022
DOI: 10.1021/acssuschemeng.2c00713
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Polyethylene Glycol Ubiquinol Succinate-Bound N-Heterocyclic Carbene–Gold(I) Complexes: Sustainable Micellar Catalysis in Water

Abstract: An efficient synthesis of three amphiphilic polyethylene glycol ubiquinol succinate (PQS)-bound N-heterocyclic carbene (NHC)−gold(I) complexes as micellar catalysts in bulk water was developed. The surfactant-bound gold catalysts were applied in three different cyclization reactions of acetylenic or allenic substrates, with the main focus being the gold-catalyzed dehydrative cyclization of alkynediols to furans. An effective recycling of the designer surfactant-bound NHC−gold(I) catalysts in water was demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Catalyst leaching, on the other hand, was recently investigated for Cat1 covalently bound to the designer amphiphile PQS. In the gold‐catalyzed cyclisation of alkynediols under micellar reaction conditions only minimal leaching from 0.3 to 8 ppm was found in 7 consecutive runs [34] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalyst leaching, on the other hand, was recently investigated for Cat1 covalently bound to the designer amphiphile PQS. In the gold‐catalyzed cyclisation of alkynediols under micellar reaction conditions only minimal leaching from 0.3 to 8 ppm was found in 7 consecutive runs [34] …”
Section: Resultsmentioning
confidence: 99%
“…[31] It has been reported that in neutral media, approximately 20 % of the ion pair is dissociated in SDS-derived micelles, which leads to an increased proton concentration on the surface of the micelles [32] that has been found to be even higher when SDS was mixed with a neutral surfactants such as a neutral poly(ethylene oxide). [33] Since the addition of pTsOH has been reported to accelerate the goldcatalyzed dehydrative cyclization of acetylenic diols to furans, [34] the same effect of Brønsted acid-catalyzed reaction acceleration may also occur in the cycloisomerization of allenes in the presence of SDS. To better understand the effect of the linker between the catalyst and polymer backbone additional kinetic studies were performed on the cycloisomerisation of allene 1 a to the furan 2 a.…”
Section: Chemcatchemmentioning
confidence: 99%
See 1 more Smart Citation
“…Without SDS, the catalyst could be reused seven times. Although some loss in reactivity was observed as the time required for full conversion increased from 5 to 20 h [ 72 ]. Similarly, Lipshutz and colleagues used the PQS platform with a ruthenium-based catalyst (a Hoveyda-Grubbs catalyst).…”
Section: Designer Surfactantsmentioning
confidence: 99%
“…This compartmentalization strategy is inspired by enzymes that use microcompartments to carry out many biocatalytic transformations in mild conditions. , The unique regio-, stereo-, and enantioselectivities shown by enzymes result from their precise three-dimensional structure and the specific placement of active functions in their core. Significant efforts have been made to replicate this activity in synthetic polymer structures. Several groups have thus designed compartmentalized nanostructures that allow reactions to take place in appropriately designed microenvironments. Taking inspiration from these studies, we designed a block copolymer that self-assembles in water to produce a micellar nanostructure, in which covalently linked benzimidazolium acetate-type entities are compartmentalized within the hydrophobic core (Figure c).…”
Section: Introductionmentioning
confidence: 99%